Pengaruh Komunitas Online Dan Pemasaran Digital Dengan Keinginan Bermain Terhadap Loyalitas Pengguna Game Online Mobile Legend Di Surabaya - Steven Paul Tarigan; Diah Ayu Sanggarwati; Leonard Adrie Manafe (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This research aims to analyze the influence of online communities and digital marketing on the desire to play and loyalty of users of the Mobile Legends online game in Surabaya. This research uses quantitative methods by collecting data through online questionnaires from 100 respondents who are members of the Mobile Legends community in Surabaya. The data analysis technique used is path analysis, as well as the Sobel test to test intervening variables. The results of this study indicate that online communities and digital marketing have a direct impact on user loyalty, but the desire to play does not mediate this relationship. Thus, digital marketing strategies and online community development can directly increase user loyalty without having to increase the desire to play